Analysis of influence of mode and geometric chrate-ristics on processes of high-frequency inductive plasma torch with reverse vortex flow - Serbin, S. I.; Сербин, C. И.; Mostipanenko, A. B.; Мостипаненко, А. Б. (My University, 2014)
The analysis of aerodynamic and heat structure of flow in high-frequency inductive plasma torch has been carried out. The range of plasma torch power is measured in dozens of kilowatts. The numerical simulation methods of the turbulent flow in the plasma torch affected by high frequency electromagnetic field without considering the chemical kinetics are used during the research. The data of temperature field and induced current density in the plasma torch depending on current amperage and frequency are obtained. Also, these data are obtained depending on the flow scheme in the operated on argon and air plasma torches. The inductive plasma torches can be applied to solve a wide range of tasks such as activa-tion of coal-dust mixture with its further gasification, coating process for the stabilization of combustion processes as well as for the recycling processes at the mobile seaport recycling complexes. The calculations demonstrated convincingly the advantage of the operation of plasma torches with reverse vortex flow over plasma torches with “direct” vortex flow. Moreover the ob-tained data allow executing the assessment of thermal efficiency of inductive plasma jet and obtaining its optimal operational modes.
Анализ влияния режимных и геометрических характеристик на параметры высокочастотного индукционного плазмотрона с «обратным» вихрем
Serbin, S. I. Analysis of influence of mode and geometric chrate-ristics on processes of high-frequency inductive plasma torch with reverse vortex flow = Анализ влияния режимных и геометрических характеристик на параметры высокочастотного индукционного плазмотрона с «обратным» вихрем / S. I. Serbin, A. B. Mostipanenko // Shipbuilding & Marine Infrastructure. – 2014. – № 2 (2). – P. 122–130.
Keywords: plasma; combustion; numerical methods; plasma torch; плазма; горение; численные методы; плазмотрон